Living wills: would sick people change their minds?. Issue 829 (November 1994) - Potter, J. M.; Stewart, D.; Duncan, G.
Abstract : Patients admitted acutely to a geriatric medical unit were interviewed on admission about their opinions on cardiopulmonary resuscitation (CPR). They underwent a general examination and their mental health was documented by completing the geriatric depression scale. Those who did not wish CPR in the event of a cardiac arrest were questioned again on recovery. Of 216 patients admitted, only three objected to answering the questions and after the other exclusion criteria were applied, 100 patients were included in the study. A total of 92% of patients wished CPR in the event of a cardiac arrest. The 8% who did not wish CPR contained more people scoring high on the geriatric depression scale. After recovery, three of that eight had changed their minds and wished CPR if required. Patients who are acutely unwell may make decisions that are influenced by their condition at this point in time and it is important to recognize that these decisions may not be maintained. In this study, consultant geriatricians did not reflect their patients' desires in making decisions about who should receive CPR if required.